Volume 1: Symposia 2015
DOI: 10.1115/ajkfluids2015-3125
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of a Supersonic Steam Ejector for Refrigeration Application

Abstract: Supersonic steam ejectors are widely used in many industrial applications, for example for refrigeration and desalination. The experimental evaluation of the flow field inside the ejector is relatively difficult and costly due to the occurrence of shock after the velocity of the steam reaches over the sonic level in the ejector. In this paper, numerical simulations are conducted to investigate the detailed flow field inside a supersonic steam (water vapor being the working fluid) ejector. The commercial comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In the first instance, a geometry / a supersonic ejector model is taken from the literature, [39] which is shown in Figure 18 indicating the dimensions and geometry of the ejector used for this study [16].…”
Section: Validation Of the Computational Methods And Tools -Part Imentioning
confidence: 99%
See 2 more Smart Citations
“…In the first instance, a geometry / a supersonic ejector model is taken from the literature, [39] which is shown in Figure 18 indicating the dimensions and geometry of the ejector used for this study [16].…”
Section: Validation Of the Computational Methods And Tools -Part Imentioning
confidence: 99%
“…In addition to dimensional and geometrical properties ( Figure 18), operating conditions as well as the non-dimensional design parameters of the present system is also given in Table 1 and Table 2. For the test case used in this study, the system operates with a primary flow of pressure 743000 Pa, a secondary flow of pressure 86300 Pascal and a discharge pressure of 137000 Pa, same as used in the literature [39]. Figure 18.…”
Section: Validation Of the Computational Methods And Tools -Part Imentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 showed the contours of ejector's Mach number at on-design regime. Many researchers claimed that the length of mixing chamber does not significantly affect to performance of ejector [2] [13]. However, it was observed that the length of mixing chamber help stabilize ejector's entrainment ratio, means the performance remains stable while working pressures change in a limited values.…”
Section: Relation Between Entrainment Ratio and Turbulence Kinetic Enmentioning
confidence: 99%
“…Sriveerakul et al [35,36], Yuan et al [26] and Aly et al [37] comprehensively analysed and discussed the variation of the pumping performance under different geometric and operating parameters. A better understanding of the mixing process of the working steam and the pumped steam under different back pressure was studies by Su and Agarwal [38]. According to the work of Dong et al [27], a higher COP can be obtained by decreasing the temperature of primary steam and raising the temperature of secondary steam.…”
Section: Introductionmentioning
confidence: 99%